Evaluation of temperature effect on cyclic fatigue resistance of nickeltitanium instruments in a double-curved canal: a comparative study - Jumaa, Zainab Mohammed; Shukri , Biland Mohammed Salim (Brazilian Dental Science, 2022)
Objective: To investigate the effect of room and body temperatures on cyclic fatigue resistance of three endodontic nickel-titanium rotary files: Hyflex EDM (HEDM) (Coltene/Whaledent, Switzerland), WaveOne Gold (WOG) (Dentsply Maillefer, Switzer), and EdgeOne Fire (EOF) (EdgeEndo, Albuquerque, New Mexico, USA) in a doublecurved canal. Material and Methods: In this study, Sixty NiTi rotary files were used. These files were divided into three groups (n = 20 for each group). Group A: HEDM (size 25, taper 0.08), group B: WOG (size 25, taper 0.07), and group C: EOF (size 25, taper 0.07). Each group was subdivided into two subgroups (n=10 for each subgroup). One of the subgroup was subjected to cyclic fatigue test at room temperature (20±1°C), while the other subgroup was subjected to cyclic fatigue test at body temperature (37±1°C). These files were tested by using a custom-made artificial canal with a double curvature (coronal curve: 60° curvature with 5 mm radius; apical curve: 70° curvature with 2 mm radius). All instruments were rotated according to the manufacturer instructions until the fracture occurred by using electric endodontic motor (Wave One, Dentsply Maillefer, Ballaigues, Switzerland). The number of cycles to fracture (NCF) and the fractured fragment length (FL) were recorded for each endodontic file. The data were gathered and statistically analyzed using shapiro-wilk test and two-way ANOVA test. The statistical significance was set at 0.05. Results: The NCF of WOG and EOF were significantly lower at body temperature as compared to room temperature (p<-0.05), whereas no difference was observed in NCF of HEDM at body and room temperatures (p>0.05). At 20±1°C, the results showed a non-significant difference between NCF of WOG and EOF (p>0.05), while the NCF of HEDM was significantly lower than the other groups (p<-0.05). At 37±1°C, the results showed a non-significant difference in NCF among the tested endodontic files (p<-0.05). There is non-significant difference in FL of each group at (20±1°C) and (37±1°C) (p>0.05). No statistical difference in FL among the tested files at room and body temperatures (p>0.05). Conclusion: The temperature has a significant effect on cyclic fatigue resistance of EOF and WOG, whereas no effect was observed on cyclic fatigue resistance of HEDM. WOG and EOF had a comparable NCF, while HEDM had a lower NCF than other groups at room temperature. At body temperature, all tested files have a comparable NCF. These results were attributed to the type of the alloy and heat treated that was used to manufacture these endodontic files. The cyclic fatigue test should be done at body temperature. KEYWORDS Body temperature; Cyclic fatigue; EdgeOne fire; Hyflex EDM; WaveOne Gold.